Social construction of husband of female migrant workers on children’s education - Purwanto Purwanto; Dima Bassam el Hariri (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2020)
The implementation of children’s education in the family of female migrant workers (TKW) is slightly different from other families in which it relies in the hand of the fathers because the mothers are working abroad. Generally, children in such families are prone to problems either with the parents, in education, and/or in health due to the absence of the mother. This study utilizes Berger’s social construction theory to analyze how children’s education in such families are managed and conducted by the fathers. In order to do so, the research was designed as a qualitative research taking location in the village of Deyeng, in the district of Ringinrejo of Kediri known for its residents’ high participation as TKW. Data were collected from in-depth interviews from informants selected using purposive sampling. Results show that, firstly, the fathers understand children’s education as a shared responsibility with a bigger portion leaning to the mothers. This is due to perceived differences that the mothers tend to have stronger emotional attachment, perseverance, and patience to perform the task. Second, children’s education are conducted by the fathers in the forms of teaching them to read, write, and draw; instilling norms of politeness, discipline, and religious values; and admitting the children to tutoring institutions and Islamic religious tutoring services. Third, the fathers adaptability to the mothers’ leaving highly affects the process of children’s education, either in terms of economic background of the family, the fathers’ role in the children’s education, the fathers’ employment status, and difference in the children’s education level.